A STUDY ON LANGUAGE LEARNING STRATEGIES USED BY INTERNATIONAL CLASS STUDENTS AT FACULTY OF LAW UNIVERSITAS BRAWIJAYA - AYUNINGTYAS, DAHLIA SRITANJUNG (Jurnal Ilmiah Mahasiswa FIB, 2014)
Nowadays English is known as an international language that has beenused for communication. Considering English has an important role ininternational communication, most of students in Indonesia have learnt Englishfrom elementary level to tertiary level. So, English becomes a compulsary subject in Indonesia, as a foreign language in Indonesia learning English is not always easy. There are some factors that can affect language learning, one of those factors is learning strategy. This study was conducted to investigate the application of learning strategies and to examine the most frequently language learning strategy used by 2010 academic students of international class program at Faculty of Law Universitas Brawijaya in English learning process. This study used descriptive quantitative approach. The participantsinvestigated were 25 students of 2010 academic year at Faculty of LawUniversitas Brawijaya. The data were taken from Strategy Inventory for Language Learning (SILL) questionnaire completed by the students.The result reveals that the use of overall language learning strategies falls into medium level, meaning that the students sometimes used those strategies. In particular, metacognitive strategies are found as the most frequently used strategies, followed by social, compensation, cognitive, affective and memory strategies. In conclusion, based on the scores, it shows that the types of learningstrategies almost have the same level of usage from each type. Meanwhile, there is still have the most frequently learning strategy that have been used by the students, from the six types of learning strategies that is metacognitive strategy. The writer suggests the English lecturers can help the students to understand more about the importance of language learning strategies, or give the students training to be able to apply them in the learning activity. Further researchers are also suggested to use other variables of individual differences of language learning strategy in conducting research. Keywords : language learning strategies, international class students, Strategy Inventory for Language Learning (SILL) questionnaire.